2023
DOI: 10.2337/cd22-0096
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Persistence, Adherence, Hypoglycemia, and Health Care Resource Utilization in People With Type 2 Diabetes Who Continued With the Second-Generation Basal Insulin Analog Insulin Glargine 300 Units/mL or Switched to a First-Generation Basal Insulin (Insulin Glargine 100 Units/mL or Detemir 100)

Abstract: People with type 2 diabetes receiving a second-generation basal insulin (BI) analog may be switched to a first-generation formulation for financial reasons or changes in health insurance. However, because second-generation BI analogs have more even pharmacokinetic profiles, longer durations of action (>24 vs. ≤24 hours), and more stable action profiles than first-generation BI analogs, such a change may result in suboptimal treatment persistence and/or adherence. This study compared treatment persistenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…A systematic review and meta-analysis comparing the adherence and persistence rates across different medication classes for diabetes reported better adherence and persistence with the use of long-acting analogues than with human insulins [ 89 ]. Another retrospective observational analysis showed that continuing second-generation analogues was associated with a lower risk of discontinuation than first-generation analogues [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis comparing the adherence and persistence rates across different medication classes for diabetes reported better adherence and persistence with the use of long-acting analogues than with human insulins [ 89 ]. Another retrospective observational analysis showed that continuing second-generation analogues was associated with a lower risk of discontinuation than first-generation analogues [ 90 ].…”
Section: Discussionmentioning
confidence: 99%